2016
DOI: 10.1017/dmp.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable, But Why? Post-Traumatic Stress Symptoms in Older Adults Exposed to Hurricane Sandy

Abstract: Our findings indicated that because vulnerable adults can be identified before disaster strikes, the opportunity to mitigate disaster-related PTSD exists through identification and resource programs that target population subgroups. (Disaster Med Public Health Preparedness. 2016;10:362-370).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…In a metaanalysis of 2849 abstracts and 66 articles on the health sequelae of responding to various types of disasters, they found that PTSD had a reported prevalence of up to 34% in some studies, and depression was found in up to 53% of responders. Heid et al 23 assessed factors associated with PTSD in 88 older adults exposed to Hurricane Sandy. They concluded that symptoms were much more likely in elderly persons affected by Hurricane Sandy who had lower levels of income, positive affect, employment, and other factors.…”
Section: Conducted a Retrospective Analysis Between September 2000 Anmentioning
confidence: 99%
“…In a metaanalysis of 2849 abstracts and 66 articles on the health sequelae of responding to various types of disasters, they found that PTSD had a reported prevalence of up to 34% in some studies, and depression was found in up to 53% of responders. Heid et al 23 assessed factors associated with PTSD in 88 older adults exposed to Hurricane Sandy. They concluded that symptoms were much more likely in elderly persons affected by Hurricane Sandy who had lower levels of income, positive affect, employment, and other factors.…”
Section: Conducted a Retrospective Analysis Between September 2000 Anmentioning
confidence: 99%
“…Older adults with chronic illness and disabilities are particularly vulnerable to poor physical and mental health outcomes after a natural disaster. 1 Despite their known vulnerability, little research evidence exists regarding older adults' health care utilization during the year after a natural disaster.…”
mentioning
confidence: 99%
“…45 However, there may be some added benefit to sustaining this collective approach by building social capital among neighbors. 23 Building social connections and resources for older adults disconnected within their communities may diminish the vulnerability that some older adults face and promote longerterm recovery for individuals and communities. For example, efforts such as those conducted through PROSPER, a multifaceted, collaborative community-level intervention designed to draw upon evidence-based prevention programs to build social capital, may offer insight into how to build lasting social relations among communities for older persons.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,22 Older adults who lack physical and psychological capacities or resources before a disaster may be at greater risk after the disaster. 23…”
Section: The Impact Of a Natural Disaster On Older Adultsmentioning
confidence: 99%